Contributions to the Theory of Elliptic Boundary Value Problems and Their Applications in Fluid Mechanics - ALBIȘORU, Andrei-Florin (Presa Universitară Clujeană, 2026)
The purpose of this monograph is the treatment of important elliptic boundary value problems for systems of partial differential equations (PDEs) that arise in Fluid Mechanics by using the methods of potential theory and a fixed point theorem. We have treated various boundary value problems as the Dirichlet, Robin-Dirichlet, transmission, Robin-transmission in the linear case as well as the non-linear case.